2021
DOI: 10.3390/nu13051608
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maternal Stress and Glucocorticoid Rhythmicity in Human Milk

Abstract: Background: Chronic stress is often accompanied by alterations in the diurnal rhythm of hypothalamus–pituitary–adrenal activity. However, there are limited data on the diurnal rhythmicity of breast milk glucocorticoids (GCs) among women with psychological distress. We compared mothers who sought consultation at an expertise center for pregnant women with an increased risk of psychological distress with control mothers for GC diurnal rhythmicity in milk and saliva obtained at the same time. Methods: We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
3
18
1
Order By: Relevance
“…According to the foetal programming hypothesis, it can be concluded that when a woman suffers from depression during pregnancy this information is passed on through cortisol to babies who can adapt their behavioural phenotype to the future environment in which they will grow up after birth. This means that women with higher levels of cortisol in breast milk experience more negative emotions in their lives or suffer from depression [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the foetal programming hypothesis, it can be concluded that when a woman suffers from depression during pregnancy this information is passed on through cortisol to babies who can adapt their behavioural phenotype to the future environment in which they will grow up after birth. This means that women with higher levels of cortisol in breast milk experience more negative emotions in their lives or suffer from depression [36].…”
Section: Discussionmentioning
confidence: 99%
“…3). In turn, Seth et al [36] in their systematic literature review indicate a relationship between cortisol levels and postpartum depression. Groër et al [37] assessed the level of cortisol after delivery and viewed postpartum depression as a categorical variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found a relation between maternal hostility and milk cortisol concentrations (Hart et al, 2004). However, a recent study found no significant difference in breast milk glucocorticoid circadian rhythm between mothers seeking consultation for psychiatric complaints and a control group with no mental health issues (Romijn et al 2021). Interestingly, an RCT demonstrated that relaxation therapy reduced maternal stress and hindmilk cortisol concentrations in the early postnatal period (2 weeks), but no effect on milk cortisol was found later on.…”
Section: Maternal Mental Healthmentioning
confidence: 99%
“…Cortisol released in the systemic circulation appears to be the primary source of BM cortisol concentrations, as BM cortisol was shown to be strongly correlated with plasma cortisol concentrations [26,40]. Maternal stress is a substantial factor influencing higher cortisol concentrations in BM [23,[41][42][43]. Although BM glucocorticoids were first detected in the 1970s [44], few studies to date have looked at their effects on the offspring [26].…”
Section: Introductionmentioning
confidence: 99%